CoMFA, Molecular Docking and Molecular Dynamics Studies on Cycloguanil Analogues as Potent Antimalarial Agents - Isman Kurniawan; Muhammad Salman Fareza; Ponco Iswanto (Universitas Gadjah Mada, 2021)
Malaria is a disease that commonly infects humans in many tropical areas. This disease becomes a serious problem because of the high resistance of Plasmodium parasite against the well-established antimalarial agents, such as Artemisinin. Hence, new potent compounds are urgently needed to resolve this resistance problem. In the present study, we investigated cycloguanil analogues as a potent antimalarial agent by utilizing several studies, i.e., comparative of molecular field analysis (CoMFA), molecular docking and molecular dynamics (MD) simulation. A CoMFA model with five partial least square regressions (PLSR) was developed to predict the pIC50 value of the compound by utilizing a data set of 42 cycloguanil analogues. From statistical analysis, we obtained the r2 values of the training and test sets that were 0.85 and 0.70, respectively, while q2 of the leave-one-out cross-validation was 0.77. The contour maps of the CoMFA model were also interpreted to analyze the structural requirement regarding electrostatic and steric factors. The most active compound (c33) and least active compound (c8) were picked for molecular docking and MD analysis. From the docking analysis, we found that the attached substituent on the backbone structure of cycloguanil gives a significant contribution to antimalarial activity. The results of the MD simulation confirm the stability of the binding pose obtained from the docking simulations.